Glymphatic dysfunction mediates the influence of choroid plexus enlargement on information processing speed in patients with white matter hyperintensities - Xu, Yanan; Wang, Mengxue; Li, Xiaoli; Lu, Tong; Wang, Yanjuan; Zhang, Xuezi; Wang, Zan; Yan, Fuling (Cerebral cortex (New York, N.Y. 1991), 2024)
Abstract Glymphatic dysfunction has been correlated with cognitive decline, with a higher choroid plexus volume (CPV) being linked to a slower glymphatic clearance rate. Nevertheless, the interplay between CPV, glymphatic function, and cognitive impairment in white matter hyperintensities (WMHs) has not yet been investigated. In this study, we performed neuropsychological assessment, T1-weighted three-dimensional (3D-T1) images, and diffusion tensor imaging (DTI) in a cohort of 206 WMHs subjects and 43 healthy controls (HCs) to further explore the relationship. The DTI analysis along the perivascular space (DTI-ALPS) index, as a measure of glymphatic function, was calculated based on DTI. Severe WMHs performed significantly worse in information processing speed (IPS) than other three groups, as well as in executive function than HCs and mild WMHs. Additionally, severe WMHs demonstrated lower DTI-ALPS index and higher CPV than HCs and mild WMHs. Moderate WMHs displayed higher CPV than HCs and mild WMHs. Mini-Mental State Examination, IPS, and executive function correlated negatively with CPV but positively with DTI-ALPS index in WMHs patients. Glymphatic function partially mediated the association between CPV and IPS, indicating a potential mechanism for WMHs-related cognitive impairment. CPV may act as a valuable prognostic marker and glymphatic system as a promising therapeutic target for WMHs-related cognitive impairment.